2020
DOI: 10.3389/fgene.2020.00652
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Long Non-coding RNAs and Circular RNAs in Porcine Milk Exosomes

Abstract: RNA in milk exosomes can be absorbed in the mammalian intestinal tract and function in gene expression regulations. Our previous work demonstrated that porcine milk exosomes (PME) contain large amounts of miRNAs and mRNAs. Increasing evidence suggests that long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs) are of particular interest, given their key role in diverse biological processes of animals. However, the expression profiles and the potential functions of lncRNAs and circRNAs in PME are still unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 77 publications
0
28
0
Order By: Relevance
“…Studies of the past decade have shown the content of various noncoding RNA—microRNA, long noncoding RNA, circular RNA [ 60 ]—in bovine [ 61 ], human [ 62 ], panda [ 12 ], porcine [ 7 ], and rat [ 63 ] milk. Exosomal RNAs are stable at low intestinal pH values and in the presence of RNases [ 61 , 64 ].…”
Section: Bioactive Compounds Of Milk Exosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the past decade have shown the content of various noncoding RNA—microRNA, long noncoding RNA, circular RNA [ 60 ]—in bovine [ 61 ], human [ 62 ], panda [ 12 ], porcine [ 7 ], and rat [ 63 ] milk. Exosomal RNAs are stable at low intestinal pH values and in the presence of RNases [ 61 , 64 ].…”
Section: Bioactive Compounds Of Milk Exosomesmentioning
confidence: 99%
“…It releases mammary epithelial acinus from cell arrest during morphogenesis [ 115 ], suggesting a potential effect of mammary miR-21 on tumor growth processes. Long noncoding RNA of porcine milk exosomes may interact with miRNA related to cell proliferation, and circular RNA may target miRNA associated with intestinal cells [ 60 ]. A recent paper showed that miRNAs from bovine and porcine milk were adsorbed in piglet intestine and transported to the blood serum with different efficiencies [ 92 ].…”
Section: Biological Activity Of Milk Exosome Nucleic Acids and Delmentioning
confidence: 99%
“…The role of non-coding RNAs (ncRNAs) in EVs is not fully understood, but their higher abundance in association with cancer and other diseases demonstrated their relevance. Several studies are underway on microRNAs, long ncRNAs, and circular RNA present in exosomes, and evidence exists that non-protein coding genes harbors crucial importance in terms of development, homeostasis, and disease [ 249 , 250 , 251 , 252 , 253 , 254 ].…”
Section: The Potential Use Of Iace For Extracellular Vesicle Studimentioning
confidence: 99%
“…On the one hand, some studies have shown that cir-cRNAs play an important role in regulating the lactation of livestock [3][4][5]. Some studies detected a total of 37,818 circRNAs in goat breast tissue, of which 864 circRNAs were differentially expressed, 611 were upregulated, and 253 were down-regulated [6], so they speculated that these circRNAs may be related to breast development and lactation.…”
Section: Introductionmentioning
confidence: 99%